How Self-Regulated Learning Strategies Influence Writing Performance Among Working Graduate Students - Alvioreta, Fara; Slamet Setiawan; Ahmad Munir (E-Link Journal, 2025)
This research examines how self-regulated learning strategies influence stress levels, motivation, and time management among working graduate students, specifically regarding their writing abilities. The investigation addresses ongoing debates about whether employment helps or hinders academic success for graduate students. A qualitative approach was employed using open-ended questionnaires distributed to English Education graduate students working full-time or part-time. This method enabled efficient data collection within a limited timeframe while maintaining depth of insight. The smaller sample size typical of qualitative research allowed for detailed analysis of participant experiences and strategies. With the majority of graduate students now balancing employment alongside their studies, understanding effective learning strategies becomes increasingly crucial. Previous research presents conflicting findings: some studies suggest that working negatively impacts academic performance, while others demonstrate that employed students can maintain high achievement levels through strategic approaches to learning. Results support that employed graduate students can excel academically when implementing effective self-regulated learning techniques. Participants demonstrated exceptional writing performance, evidenced by their published scholarly articles. These outcomes suggest that strategic time management, motivation maintenance, and stress reduction techniques enable working students to produce high-quality academic work. The findings challenge assumptions about employment as a barrier to academic excellence. Instead, they highlight how purposeful learning strategies can help graduate students successfully navigate the dual demands of work and academic responsibilities, particularly in writing-intensive disciplines. This research contributes valuable insights for supporting the growing population of employed graduate students.